Scalable flibanserin nanocrystal-based novel sublingual platform for female hypoactive sexual desire disorder: engineering, optimization adopting the desirability function approach and in vivo pharmacokinetic study - Marianne J. Naguib; Amal I. A. Makhlouf (Taylor & Francis Group, 2021)
Flibanserin (FLB) was approved by FDA for the treatment of pre-menopausal female hypoactive sexual desire disorder (HSDD). FLB suffers from low oral bioavailability (33%) which might be due to hepatic first-pass metabolism in addition to its poor aqueous solubility. The sublingual route could be a promising alternative for FLB due to the avoidance of enterohepatic circulation. However, the drug needs to dissolve in the small volume of saliva in order to be absorbed through the sublingual mucosa. Therefore, FLB nanocrystals were prepared by sono-precipitation technique according to 23 full factorial design. FLB-nanocrystals were formulated using two surfactants (PVP K30 and PL F127) in two different amounts (200 and 400 mg) and the volume of ethanol was either 3 or 5 mL. Nanocrystal formulation was optimized according to the desirability function to have a minimum particle size, zeta potential, polydispersity index, and maximum saturated solubility. The optimized formula had a particle size of 443.12 ± 14.91 nm and a saturated solubility of 23.27 ± 4.62 mg/L which is five times the saturated solubility of FLB. Nanocrystal dispersion of the optimized formula was solidified by freeze-drying and used to prepare rapidly disintegrating sublingual tablets containing Pharmaburst® as superdisintegrant. Sublingual tablet formulation with the shortest disintegration time (36 s) was selected for the in vivo study. FLB nanocrystal-based sublingual tablets exhibited a two-fold increase in bioavailability with a faster onset of action compared to the commercially available oral formulation. These findings prove the potential application of FLB nanocrystal-based sublingual tablets in the treatment of HSDD.